The Development of Cassava Agribusiness in Lampung Province (The Implications for The Cassava Agribusiness Partnership Model) - Wan Abbas Zakaria; Teguh Endaryanto; Lidya Sari Mas Indah; Dedy Hermawan (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Cassava agribusiness has several problems and obstacles that must be overcome completely. So yet, no institutional method of transaction is compatible with and advantageous to all cassava agricultural stakeholders. The objective of this research was to look at the cassava agribusiness partnership model in Lampung and placed study in three districts in Lampung Province, each with its distinctive characteristics: Central Lampung, East Lampung, and West Tulang Bawang. Primary and secondary data were used in the study. In this study, survey methods and in-depth interviews were utilized to obtain data. Qualitative descriptive analysis with an institutional perspective was used to analyze this study. The findings revealed that institutional collaboration in sustainable partnerships between farmer groups associations (Gapoktan), factories with third-party help, and an ICT system could improve the farm, factory, and overall cassava agribusiness performance. Keywords: institutional, partnership, agribusiness, cassava, farmer